S Parameter Computation and Their Use for Electromagnetic Energy Wireless Transmission - Stanculescu, Marilena; Iordache, Mihai; Niculae, Dragos Niculae; Iordache, Lavinia; Bucata, Victor (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper present the correct way of defining S parameters, based on linear electrical circuits, and the practical use of these parameters in obtaining efficient processes for transmitting the information and of the electromagnetic energy wireless transfer from emitter-receiver signal transmission point of view. Here are presented, also, two procedures for calculating these parameters, one based on modified nodal analyses, the second one based on state equations method. S parameters generation algorithm has the same structure for both computation procedures. The computation procedures for S parameters use the most advanced analogue circuit simulation programs, such as: Cadence, Advances Design System, Ansoft Extractor Q3D, Feko, ECAP, SYSEG etc. Finally, there are presented a few illustrative examples that certify the validity of the used computation procedures.